Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/plants8100397
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Characterization of a Soybean (Glycine max) Thioesterase that Acts on Intermediates of Fatty Acid Biosynthesis

Abstract: (1) Background: Plants possess many acyl-acyl carrier protein (acyl-ACP) thioesterases (TEs) with unique specificity. One such TE is methylketone synthase 2 (MKS2), an enzyme with a single-hotdog-fold structure found in several tomato species that hydrolyzes 3-ketoacyl-ACPs to give free 3-ketoacids. (2) Methods: In this study, we identified and characterized a tomato MKS2 homolog gene, namely, GmMKS2, in the genome of soybean (Glycine max). (3) Results: GmMKS2 underwent alternative splicing to produce three al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 96 publications
(124 reference statements)
0
2
0
Order By: Relevance
“…R5 seeds showed higher levels of short‐chain ACPs but upon reaching the R6 stage of development there was a larger accumulation of C14 ACP. This is relevant when considering C14 ACP is the longest acyl‐ACP without a chain‐specific thioesterase in soybean (Jones et al ., 1995; Tran et al ., 2019; Zhou et al ., 2021) and possibly results from increased nonspecific FATA/B thioesterase activity when lipid production is starting to decline as seed development progresses. Total acyl‐ACPs and relative level of oil production dropped concomitantly indicating that the quantities of these fatty acid intermediates may be a marker for active lipid production.…”
Section: Discussionmentioning
confidence: 99%
“…R5 seeds showed higher levels of short‐chain ACPs but upon reaching the R6 stage of development there was a larger accumulation of C14 ACP. This is relevant when considering C14 ACP is the longest acyl‐ACP without a chain‐specific thioesterase in soybean (Jones et al ., 1995; Tran et al ., 2019; Zhou et al ., 2021) and possibly results from increased nonspecific FATA/B thioesterase activity when lipid production is starting to decline as seed development progresses. Total acyl‐ACPs and relative level of oil production dropped concomitantly indicating that the quantities of these fatty acid intermediates may be a marker for active lipid production.…”
Section: Discussionmentioning
confidence: 99%
“…21 More TEs have been identified since we first classified TEs into families, some which form part of existing families. As examples, (a) guanosine diphosphate regulation TEs from Neisseria meningitidis appear in TE6 22 ; (b) acyllipid thioesterase from Arabidopsis thaliana in TE9 23 ; (c) methylketone synthases, 24 which were originally characterized from tomato prior to the ThYme database, have also been found in Solanum melongena and Glycine max and form part of TE9 25,26 ; (d) Shewanella oneidensis YbgC, which was found to primarily hydrolyze short chain acyl-CoA thioesters, also forms part of TE9 27 ; (e) BorB, required for borrelidin biosynthesis, is a member of TE18 28 ; and (f) the Isochrysis galbana thioesterase/ carboxylesterase (IgTeCe) is in TE21. 29 Structural knowledge about how enzymes perform thioester hydrolysis has increased; an insightful, recent review describes TE structures, with a particularly useful and clear connection of catalytic residues with enzyme topology.…”
Section: Introductionmentioning
confidence: 99%
“…The inactivity of our GmALT1 expression construct was later traced to the use of the coding sequence from a splice variant that is apparently inactive, but nonetheless highly expressed in plant tissues according to transcriptomic data (Severin et al, 2010). Tran et al (2019) identified and characterized an active GmALT1 isoform through heterologous expression in E. coli bacteria. The most abundant product of this active GmALT1 isoform was 14:1 β-keto fatty acid (converted to 13:1 MK during sample treatment), therefore,…”
Section: -Alt Enzymes Can Be Grouped According To Their Catalytic Pre...mentioning
confidence: 99%
“…The Group 1 ALTs identified in this study may also function in plant-wide insect defense given their broad substrate specificities. It is worth noting that the single ALT genes of V. vinifera and G. max also encode for Group 1 ALTs with broad, plant-wide expression patterns according to publicly available transcriptomic data (Fasoli et al, 2012;Severin et al, 2010;Libault et al, 2010;Tran et al, 2019). This suggests that in plants that possess only one ALT gene, the encoded enzyme plays a broad role in plant defence by producing a wide range of volatile compounds, while plants with multiple ALTs have evolved paralogs to fulfill specific roles.…”
Section: -Potential Biological Roles Of Alt Enzymesmentioning
confidence: 99%
See 1 more Smart Citation